Upaya Meningkatkan Keaktifan Dan Hasil Belajar Ekonomi Dengan Menggunakan Strategi ActiveKnowledge Sharing Pada Siswa Kelas Viii B SekolahMenengah Pertama Negeri 3 Gabus GroboganTahun Ajaran 2016/2017 - Riyanto, Loso, Drs. Djoko Suwandi, M.Pd (2017)
The purpose of this research is to increase the activeness and the learning outcome of economics in the 8th grade students of SMP Negeri 3 GabusGrobogan through a strategy of Active Knowledge sharing. Type of research isClass Action Research which was conducted as many as two cycles. Each cycleconsists of four stages, they are: planning, action implementation, observation,and Reflection. Subjects of this research are the 8th grade students of SMP Negeri 3 Gabus as many as 25 students. The technique of data collection used thetechniques of observation, interview and documentation. The technique of dataanalysis comparing variabble and drawing conclusion.Based on the results of the research, it is obtained the data of the students'learning activeness before the action is as much as 18%. Meanwhile, from theresults of the strategy implementation of Active Knowledge sharing in cycle Iincreases as much as 41,5%, cycle II increases into 77%. For the students'learning outcome before the action is as much as 56%, in cycle I is as much as64% and cycle II is as much as 88%.From the above data, it can be concluded that the implementation of the strategy of Active Knowledge sharing can increase the activeness and the learningoutcome of economics in the 8th grade students of SMP Negeri 3 GabusGrobogan in the academic year of 2016/2017.Keywords: Active Knowledge sharing, Learning Activeness, Students' LearningOutcome.